Piosenki - Stachura, Edward, 1937-; Vysotsky, Vladimir, 1938-1980.; Cohen, Leonard, 1934- .; Jagiello, Michal; Zembaty, Maciej (Warszawa : Mlodziezowa Agencja Wydawnicza, 1989)
A collection of songs by three internationally known composers of modern songs.
Vladimir Vysotsky's songs translated from Russian by Michal B. Jagiello and Leonard Cohen's songs translated from English by Maciej Zembaty.